Who should procreate? Selecting the best breeders through the control of marriage, Spain 1850s–1920s. - Walin, Marie (Journal of Iberian & Latin American Studies, 2023)
Prenuptial certificates were one of the most widely debated eugenicist measures in Spain, despite never having been legally adopted (as they were in several western European and Latin American countries). This article suggests antecedents for this measure by looking at arguments which developed in Spain from the 1840s that favoured controlling procreation in order to improve future generations. I aim to show how Spanish eugenics in the early twentieth century were part of a long tradition of hygienist thinking. In discussing the "positive" nature of Spanish eugenics, as described in the historiography on "Latin" eugenics, I will also shed new light on the influence of Catholicism. Due to its hold on the institution of marriage, the Catholic Church in Spain had more than a theoretical effect on eugenics; it also administered practical examples of the exclusion of individuals from procreating by investigating grounds for the annulment of marriage for reasons of impotence or insanity. In this article, I will argue that the Church acted as a model for other institutions, showing how it was possible to control procreation through legal restrictions, while maintaining privileges over the state in legislating on such issues, up to the period of the Franco dictatorship.